ANALISIS PERLAKUAN AKUNTANSI PERALATAN KANTOR DAN AKTIVA TETAP PADA PT. ASTRA SEDAYA FINANCE - Maatuil, Andika Prianto; Kalangi, Lintje; Walandouw, Stanley Kho (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
Business world is growing rapidly now requires every company or business entity to be more active in berkompetitif and continue to strive to achieve goals that have been set. The main goal of the company is to create maximum profit to increase the company's growth. Fixed assets are one of the main parts of the company's large and depreciated assets in an accounting period. The objective of this research is to know the accounting treatment of fixed assets in compliance with PSAK No. 16 Year 2015 at PT. Astra Sedaya Finance Manado. The type of research that is done is descriptive research. Based on the results of research conducted, the company set the acquisition price for fixed assets sometimes does not occur uniformity for the acquisition price of fixed assets, the management company has never done or acknowledge the decline and write-off of fixed assets while the method of depreciation is done every year against all types of assets using straight-line depreciation method consistently each year by applying the straight-line method and not deviating from generally accepted accounting standards and any purchase of fixed assets for the operations of the company are recorded at historical cost as the basis for measuring its fixed assets.Keywords : Depreciation, Fixed